2021
DOI: 10.7759/cureus.18071
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Health Care Workers in Doffing of Personal Protective Equipment Using Real-Time Remote Audio-Visual Doffing Surveillance System: Its Implications for Bio-Safety Amid COVID-19 Pandemic

Abstract: BackgroundVery little has been reported about health care workers' (HCWs) adherence to the Centers for Disease Control and Prevention (CDC) guidelines of doffing personal protective equipment (PPE) amid the COVID-19 pandemic. Real-time remote audio-visual doffing surveillance (RADS) system for assisting doffing might reduce the risk of self-contamination. We used this system to determine the incidence of the breach in biosafety during doffing of PPE among HCWs involved in the care of Covid-19 patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…A previous study showed that most of the problems associated with the PPE kit occurred during the doffing process; hence the doffing process is given the most attention in this study [ 16 ]. A survey conducted in PGIMER showed 34% errors in hand hygiene and 8% errors in N95 mask removal during the doffing process, where the facility of the doffing corridor was used [ 17 ]. One interesting finding in the doffing corridor was that HCWs simultaneously doffing at a time, helping each other follow the audio commands, and reduced the mask removal error to 2.5%, which had similarities to a previous study [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that most of the problems associated with the PPE kit occurred during the doffing process; hence the doffing process is given the most attention in this study [ 16 ]. A survey conducted in PGIMER showed 34% errors in hand hygiene and 8% errors in N95 mask removal during the doffing process, where the facility of the doffing corridor was used [ 17 ]. One interesting finding in the doffing corridor was that HCWs simultaneously doffing at a time, helping each other follow the audio commands, and reduced the mask removal error to 2.5%, which had similarities to a previous study [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Our recent experience with the RADS system, demonstrated low self-contamination rates among HCWs, amid Covid 19 pandemic. 13 As per our understanding, there is a lack of research evaluating the efficacy of remote system versus onsite buddy system of monitoring the doffing of PPE. In the present study, we intended to compare the efficiency and safety of the RADS system versus the standard onsite buddy system.…”
Section: Introductionmentioning
confidence: 99%
“… 8 In addition, healthcare professionals (HCP) had to adapt to the new disease and develop algorithms for diagnosis, risk stratification, and treatment of SARS-CoV-2. 9 11 At the same time, shortages of protective equipment had to be overcome. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, healthcare professionals (HCP) had to adapt to the new disease and develop algorithms for diagnosis, risk stratification, and treatment of SARS-CoV-2. [9][10][11] At the same time, shortages of protective equipment had to be overcome. 12,13 In the field of gastroenterology, especially endoscopy, the focus is on monitoring, diagnosing, and treating patients with chronic or acute gastrointestinal (GI) diseases.…”
Section: Introductionmentioning
confidence: 99%